The Decline of Rural Area in Romania - Economic Implications - Marius M. MICU; Catalin R. VINTU; Adina M. IORGA; Paula STOICEA (Communications of International Proceedings, 2022)
The rural area is a particularly important component from a socio-economic point of view, especially due to the high proportion of the population living in rural areas. The rural population accounts for 46.4% of Romania's total population, which is quite high compared to other countries in the European Union, where urbanization has been more pronounced. The aim of the paper is to identify the influence of the agricultural sector on the economic development of rural localities. Also, this paper analyses the main economic indicators found in Romania and in the South-Muntenia Region (a region characterised by the implications of agriculture on the economy of this area) in the context of the development of family farms as a factor that can contribute to the development of this region. In this respect, the following indicators were analysed: average number of employees by sector, salary, average monthly labour cost, relative poverty rate. To process these data, the main location and dispersion indicators were calculated.
Keywords: rural development; Romania; economic rural; development